Navigating the future: Attitudes and ethical implications of AI tools in academic research - Asagar, Mirza Shahzan (Journal of Interdisciplinary Studies in Education, 2026)
The growing use of artificial intelligence (AI) tools is transforming traditional research methods, making them more efficient, accurate, and innovative. This paper examines the awareness, usage, and ethical concerns of AI tools among postgraduate students and research scholars from various fields. This quantitative descriptive study looks into how postgraduate students and PhD researchers view the benefits, challenges, and ethical issues related to AI tools in research. A key finding is that, despite high familiarity with AI, less than one in five users utilize data-mining, predictive modeling, or visual analytics platforms. Participants rated AI's contribution to research quality highly but reported only monthly use, showing underuse despite recognizing its value.